Selection of formwork systems for arrangement of monolithic columns according to the method of integer rating of laborability and process duration - Tonkacheev, G.; Tonkacheev, V.; Nosach, K. (Ways to Improve Construction Efficiency, 2021)
The relevance of this article is related to the problem of standardization of technological processes in which there is construction equipment for concrete work. Almost all construction processes are performed using construction equipment. The arrangement of monolithic structures is accompanied by the processes of installation and dismantling of the formwork. It is impossible to make a reasonable choice of options for equipping construction processes according to the existing standard time norms. For all possible variants of column formwork, almost the same time norms are used [1]. The article considers the comparison of several formwork options for the installation of monolithic reinforced concrete columns of frame structures. To determine the duration and complexity of the process used the method of integer rationing [2], which allows taking into account even minor changes in the formwork. Calculation by this method makes it possible to select the most effective options for formwork. As a basis, this technique uses an analysis of the number of actions and responsibilities of these actions in relation to the quality of the process and its reliability. Any construction equipment is characterized by structural and technological versatility, which also affects the choice of options conditions of the process, so the article provides an analysis of these factors in terms of quality. If in the structure of the structure there are columns with different cross-sectional dimensions or heights, the preference is given to formwork options with greater structural versatility. The material of the article opens a whole direction for further research in the field of construction equipment in other processes.